A Study on the Push and Pull Factors Affecting the International Emigration Intentions of Turkish Physicians - Mustafa Amarat; Mahmut Akbolat; Oya Adıyaman (Association of Nurse Managers, 2023)
Aim: The number and distribution of health workers per capita are significant factors for countries to achieve their goals in the health sector. However, there is a global shortage of skilled health workers. The immigration of health professionals or their intention to emigrate is a critical problem, especially for source countries. This situation directly affects the access, equity, and quality of necessary health services. In this article, we discussed the intentions of physicians to emigrate and the factors that pull and push physicians, including the methods that can be applied. Method: It was designed as a descriptive and cross-sectional study in accordance with the research problem. A total of 504 physicians from Turkey participated in the study. The data were collected using a personal information form and a scale consisting of "Push Factors, Pull Factors, Negative Impacts of Migration, and Positive Impacts of Migration". Mean and standard deviation were used in the study. Results: The results indicate that physicians in Türkiye intend to emigrate. Also, physicians would prefer to emigrate to developed countries such as Germany, the USA, and England if they have the opportunity to leave Türkiye. Working and living conditions are the first factors pushing them, followed by the phenomenon of violence in healthcare. The participants think that if they emigrate, new physicians in Turkey cannot be replaced quickly, and this will further increase the heavy workload of their colleagues. Conclusion: Considering these results, it is necessary to develop policies for trained healthcare workers to work in source countries and to reduce the level of the emigration tendency of health workers, especially in developing countries such as Türkiye. In particular, these policies should include micro and macro policies related to violence in healthcare and the improvement of working conditions. Otherwise, the effective, efficient, and interrupted delivery of health services may be disrupted.